AN ANALYSIS OF DONAL J.TRUMPS REMARKS ”MY FELLOW AMERICANS” USING INTERPERSONAL METAFUNCTION - Mayang Sari; Dian Meta Ariani (IKIP Siliwangi, 2018)
The aims of this reasearch is analyzing President Donal J.Trump statement in weekly address on www.whitehouse.gov entitle “My fellow american” based on systemic functional grammar. The writers focused on interpersonal metafunction which consist of mood and speech functions. The method in this research used qualitative analysis method. The data were analyzed using mood structure analysis by M.A.K Haliday. The text entitled My Fellow American the statement by President Donal J.Trump Remarks is categorized into the text which uses declarative mood type the most (69,2%) which indicates the position o the speaker provider of information and the listeners as the recepeint of information. The clauses in the text are said by temporal deicticity or finite tense the most (89%), while the modality deicticity only appears a little (5%) which indicates that the speaker has no right to persuade the listeners because the genre of the text is narrative which functions only to telling the listeners.There are only two speech functions found in the transcipt of President Donal J.Trump are statment and question. Statement as mostly appeared in the text which reaches precentage 75% whereas question only reaches percentage 25%. So it can be concluded that speech function used in the transcipt is statement with function to give information.